Sondaż w oczach polityków. Posłowie Sejmu RP o badaniach opinii publicznej - Sułek, Antoni (Wydział Prawa i Administracji UAM, 1995)
The paper presents the results of an investigation carried out to determine how the public opinion and the knowledge learnt from the results of public surveys have influenced the members of the 2nd term Parliament of the Republic of Poland. The role of such surveys and their position among other sources of information expressing public opinion to the MPs has been analysed and the extent of the use of such knowledge determined. The degree of trust among members of the Polish parliament in the results of public opinion polls has been examined and their attitudes to the possibilities of manipulation in the survey investigated. Further, the views of the politicians with regards limitations put on the publication of survey results before elections and the possible use of pre-election surveys results in election campaigns has been presented. Finally, the opinion of MPs on the influence of such results on the attitudes and way of thinking of politicians and their electorates has been determined.
Results of publik opinion surveys in the eyes of politicians. Members of the Polish Parliament and results of the surveys